Aggregation‐induced emission of copper nanoclusters. Issue 6 (2nd September 2021) - Shi, Yu‐e; Ma, Jinzhu; Feng, Anrui; Wang, Zhenguang; Rogach, Andrey L.
Abstract: Copper nanoclusters (Cu NCs) have recently emerged as promising luminophores, featuring ultra‐small size, reasonable photostability, large Stokes shift, and long emission lifetimes. Aggregation‐induced emission (AIE) has been often used to further improve both the emission intensity and stability of these clusters, with plenty of potential applications in the fields of chemical sensing and bioimaging. This review starts with a summary of the current understanding of emission mechanisms of Cu NCs and proceeds with the analysis of contributions from the Cu metal core and the organic ligands. We summarize the recent research progress on the design of ligands, and the ways on how to induce aggregation of the Cu NCs through electrostatic charge neutralization, host‐guest interactions, and the use of templates. We also discuss the current understanding of emission mechanisms of Cu NCs experiencing AIE, such as the often‐cited restriction of intramolecular motion and contributions from Cu(I) molecular complexes. We finish this review by providing concluding remarks and offering our own perspective on the active field of AIE of Cu NCs, with a hope to further promote the research on the fundamental aspects of this useful phenomenon. Abstract : This review offers an in‐depth discussion on the origin of optical features of copper nanoclusters (Cu NCs) related to their often observed aggregation‐induced emission (AIE). It provides specific consideration on the nature of ligands to be selected for the synthesis of Cu NCs experiencing AIE, the approaches to modulate their aggregation behavior, and the AIE mechanisms.